â€œANALISIS PERBEDAAN KINERJA KEUANGAN PADA BANK PEMERINTAH DAN BANK SWASTA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI)â€ - nina yuliana sari (Jurnal Ilmu Akuntansi, 2018)
The existence of financial institutions, especially the banking sector, makes interbank competition becomes increasingly tight, especially government banks and private banks. This study aims to determine whether there is a difference between the financial performance of government banks and national private banks listed on the Indonesia Stock Exchange (IDX) using the ratio of Return of Assets (ROA), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Non Perfoming Loan (NPL). The type of data used is Quantitative data in the form of financial statements. The samples used are 23 banks listed in Indonesia Stock Exchange (IDX) with details of 4 state banks and 19 private banks. The financial statements of the 23 banks The sample is a financial report of government banks and national private banks listed on the Stock Exchange 2013-2015. Analytical technique used with t-test (Independent Sample T-Test). The results of this study indicate that there is a significant difference in the ratio of Return of Assets (ROA) in government banks and private banks. On the Net Interest Margin (NIM) ratio, Loan to Deposit Ratio (LDR) and Non Perfoming Loan (NPL), there is no significant difference in state and private banks. Based on the results of this study can be suggested to make ROA, NIM, LDR and NPL as information and as consideration of investors in investing in banking companies, because the ratio can reflect the financial performance of banks operating in a healthy so that the interests of investors awake.